Bullying and Mobbing in Academe:A Literature Review - Prevost, Chad; Hunt, Elena (European Scientific Journal, ESJ, 2018)
This review of the current state of literature in regards to academic mobbing found that the most common types of bullying were psychological and emotional attacks, often directed towards an academic by either administrators, other academics and faculty, or even students. Many risk factors are related to academic mobbing, including sex, sexual orientation, gender, race and ethnicity, rank or seniority, work experience, and age. Incidents of academic bullying often lead to multiple negative outcomes on victims, including physical, emotional and psychological damages, as well as various work-related and institutional consequences. Some coping strategies are summarized. Universities and academia in general, should help foster a culture and an environment of civility. More specifically, policies of respectful workplaces should be created and enforced, with a focus on reducing or eliminating incidents of academic mobbing.